1981
DOI: 10.1007/bf00026173
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptations to entosymbiosis in three species of graffillid rhabdocoels

Abstract: Three entosymbiotic graffillid rhabdocoels (Paravortex scrobiculariae, P. cardii and Graffilla buccinicola) from marine bivalve and gastropod molluscs show several physiological adaptations to their life-style which are intimately related to the nutritional physiology and ecology of their respective hosts.All three species feed on their hosts' partially digested food plus the cellular debris released at the end of the hosts' own digestive cycle. G. buccinicola supplements this diet by actively removing intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…This high degree of metabolic dependence may be responsible for the high specificity observed in the species of Paravortex. Regarding the turbellarian pathogenicity, no evidence of direct physical damage was observed in our study, agreeing with previous reports on bivalves infected with Paravortex (Jennings & Phillips, 1978;Jennings & Le Flore, 1979;Jennings, 1981). Although it seems to be innocuous to the host, some gravid specimens occupying a great part of the intestine lumen were observed, therefore they may reduce the absorption of the nutrients by obstruction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This high degree of metabolic dependence may be responsible for the high specificity observed in the species of Paravortex. Regarding the turbellarian pathogenicity, no evidence of direct physical damage was observed in our study, agreeing with previous reports on bivalves infected with Paravortex (Jennings & Phillips, 1978;Jennings & Le Flore, 1979;Jennings, 1981). Although it seems to be innocuous to the host, some gravid specimens occupying a great part of the intestine lumen were observed, therefore they may reduce the absorption of the nutrients by obstruction.…”
Section: Discussionsupporting
confidence: 91%
“…Since the graffilids lack endogenous digestive enzymes, they use their host enzymes to feed on partially digested hosts food, and their food reserves consist mainly on glycogen (as it occurs in Digenea and Cestoda); these facts represent physiological adaptations to a parasite mode of life (Jennings, 1981;Jennings & Phillips, 1978;Jennings & Le Flore, 1979). This high degree of metabolic dependence may be responsible for the high specificity observed in the species of Paravortex.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low intensity of infestation observed, and that not all gaping or dead scallops contained flatworms, we cannot conclude that the flatworms are the cause of the change in scallop behaviour, particularly if the flatworms are only feeding on the scallop's digested food as has been demonstrated for other Paravortex (Jennings & Phillips 1978;Jennings 1981). Some other factor may have caused the change in scallop condition and the presence of the flatworms may be simply opportunistic.…”
Section: In Most Other Examples Of Bivalves Infested Withmentioning
confidence: 81%
“…Paravortex there appears to be no evidence of direct physical damage caused to the host (Jennings & Phillips 1978;Wardle 1980;Fleming et al 1981;Jennings 1981), although the rhabdocoel Graffilla buccinicola has been found to supplement its diet of the host's partially digested food by removing intact cells from the digestive epithelium (Jennings 1981). Consequently, many of these associations have been termed as entosymbiotic.…”
Section: In Most Other Examples Of Bivalves Infested Withmentioning
confidence: 99%
See 1 more Smart Citation